Computer Graphics for All. - TAKEO IGARASHI (Communications of the ACM, 2010)
The article presents information on research into the development of user-friendly computer graphics design programs. The project is intended to make three-dimensional (3-D) and animated computer graphics easy for a non-professional to manipulate. A comparison is made to the spread of software programs which made professional-looking typefaces and printing ubiquitous. The development of prototype programs called Teddysystem and MovingSketch is described. The methods which were used to simplify the computer processing and control inputs are explained.